Feasibility, Acceptability and Preliminary Efficacy of Tikambisane ('Let's Talk to Each Other'): A Pilot Support Group Intervention for Adolescent Girls Living With HIV in Zambia. (30th June 2021) - Stangl, Anne L.; Mwale, Mwangala; Sebany, Meroji; Mackworth-Young, Constance RS; Chiiya, Chipo; Chonta, Mutale; Clay, Sue; Sievwright, Kirsty; Bond, Virginia
Background: In Zambia, 84, 959 adolescent girls and young women (AGYW) aged 15-24 are currently living with HIV. We explored the feasibility and acceptability of a 6-session, curriculum-based support group intervention designed to address key concerns of AGYW living with HIV. Setting: Urban Zambia Methods: Surveys and in-depth interviews were collected pre- and post-intervention from participants enrolled from 2 health facilities. Eight participant observations of sessions were conducted. Descriptive statistics at baseline were reported only for AGYW who participated in the intervention (N = 21), while analyses comparing baseline and endline outcome measures were restricted to participants who had data at both time points (N = 14). Results: Support groups were feasible to conduct and acceptable to participants. Co-facilitation by an adult counselor and peers living with HIV raised confidence about session content. Sessions on antiretroviral therapy (ART), disclosure and stigma, and grief and loss were most in demand. We did not observe significant differences in key outcome measures between baseline and follow-up. However, qualitative data supported the positive impact of the intervention on ART adherence and hope for the future following the intervention among our participants. Conclusion: A short-term, structured support group series holds promise for helping AGYW living with HIV safely navigate a complex time in their lives.